Selectivity of Inhibition of N-Succinyl-l,l-Diaminopimelic Acid Desuccinylase in Bacteria: The product of dapE-gene Is Not the Target of l-Captopril Antimicrobial Activity - Narasimha Rao Uda; Marc Creus (Bioinorganic Chemistry and Applications)
The emergence of bacterial strains that are resistant to virtually all currently available antibiotics underscores the importance of developing new antimicrobial compounds. N-succinyl-l,l-diaminopimelic acid desuccinylase (DapE) is a metallohydrolase involved in the meso-diaminopimelate (mDAP)/lysine biosynthetic pathway necessary for lysine biosynthesis and for building the peptidoglycan cell wall. Because DapE is essential for Gram-negative and some Gram-positive bacteria, DapE has been proposed as a good target for antibiotic development. Recently, l-captopril has been suggested as a lead compound for inhibition of DapE, although its selectivity for this enzyme target in bacteria remains unclear (Gillner et al. (2009)). Here, we tested the selectivity of l-captopril against DapE in bacteria. Since DapE knockout strains of gram-negative bacteria are viable upon chemical supplementation with mDAP, we reasoned that the antimicrobial activity of compounds targeting DapE should be abolished in mDAP-containing media. Although l-captopril had modest antimicrobial activity in Escherichia coli and in Salmonella enterica, to our surprise, inhibition of bacterial growth was independent both of mDAP supplementation and DapE over-expression. We conclude that DapE is not the main target of l-captopril inhibition in these bacteria. The methods implemented here will be useful for screening DapE-selective antimicrobial compounds directly in bacterial cultures.